2012
DOI: 10.3892/ijo.2012.1510
|View full text |Cite
|
Sign up to set email alerts
|

Preferential inhibition of hepatocellular carcinoma by the flavonoid Baicalein through blocking MEK-ERK signaling

Abstract: Abstract. Baicalein is a purified flavonoid extracted from the roots of Scutellaria baicalensis or Scutellaria radix. Although previous studies have suggested that Baicalein possesses an in vitro anti-hepatocellular carcinoma activity, its in vivo effects and mechanisms of action are still not completely understood. In this study, Baicalein at concentrations of 40-120 µM exhibited significant cytotoxicity to three hepatocellular carcinoma (HCC) cell lines but marginal cytotoxicity to a normal liver cell line i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…Several studies in the past have shown that chrysin exerts an inhibition effect on the ERK signaling cascade in different cells and thus suppresses the levels of active phosphorylated ELK1 (Gao et al, 2013;Pichichero et al, 2011). Similarly, baicalein has been reported to have an inhibitory effect on ERK1/2 phosphorylation in both in vivo and in vitro (Agarwal et al, 2009;Gao et al, 2013;Chen et al, 2013;Liang et al, 2012;Zhou et al, 2013). On the other hand opposite effects have also been reported for baicalein, baicalin and galangin, suggesting cellor tissue-specific effects (Chen et al, 2006;Lei et al, 2012;Liu et al, 2013;Zhou et al, 2009).…”
Section: Discussionmentioning
confidence: 85%
“…Several studies in the past have shown that chrysin exerts an inhibition effect on the ERK signaling cascade in different cells and thus suppresses the levels of active phosphorylated ELK1 (Gao et al, 2013;Pichichero et al, 2011). Similarly, baicalein has been reported to have an inhibitory effect on ERK1/2 phosphorylation in both in vivo and in vitro (Agarwal et al, 2009;Gao et al, 2013;Chen et al, 2013;Liang et al, 2012;Zhou et al, 2013). On the other hand opposite effects have also been reported for baicalein, baicalin and galangin, suggesting cellor tissue-specific effects (Chen et al, 2006;Lei et al, 2012;Liu et al, 2013;Zhou et al, 2009).…”
Section: Discussionmentioning
confidence: 85%
“…Apoptotic and/or necrotic cells were evaluated by Annexin V binding and propidium iodide (PI) uptake using an Annexin V-FITC/PI kit as previously described [13]. Briefly, NPC-039 cells were plated at a density of 5×10 4 cells per well into 6-well plates for 12 h. The cells were treated with various concentrations of IL-17A (0 and 50 ng/ml) and incubated at 37°C for 24 h. The cells were washed with cold PBS and resuspended in Annexin V binding buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Baicalein possessed anti-hepatocellular carcinoma activity in vitro and in vivo. Baicalein at the concentrations of 40-120 μM exerted cytotoxicity to three hepatocellular carcinoma cell lines but with little cytotoxicity to a normal liver cell line in vitro [124]. In addition, baicalin has potential beneficial effects on ischemia/reperfusion (I/R) injury in alcoholic fatty liver.…”
Section: Scutellaria Baicalensismentioning
confidence: 99%